Pemberdayaan Sumber Daya Manusia Di Bidang Keagamaan Melalui Pelatihan Peningkatan Kompetensi Menggunakan Metode Ummi Bagi Guru TPQ - Fatih, Moh. Khoirul (LPPM IAI TABAH, 2023)
The results of observations and extracting data that we conducted for the people of Kepodang Hamlet for thirty-four days, showed various phenomena that occurred. Among these phenomena, we took one of the phenomena, namely the less than optimal teaching staff of TPQ Al-Hidayah. The lack of teaching staff resulted in learning at TPQ Al-Hidayah being less than optimal. This problem was used as the focus of research in the 2018 service activities. In an effort to overcome this problem, together with the TPQ management held a training activity entitled